2022
DOI: 10.1017/s0033291722003117
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and depressive symptoms in an early adolescent cohort

Abstract: Background To explore the cross-sectional and longitudinal association between vitamin D and depressive symptoms across early adolescence. Methods This longitudinal study included 1607 early adolescents [mean (s.d.) age, 12.49 years; 972 (60.5%) males] from the Chinese Early Adolescents Cohort, recruited from a middle school in Anhui Province and followed up annually (2019–2021). Serum 25(OH)D levels were measured in both 2019 and 2021. Self-reports on depression were assessed at each of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Studies have shown that Vitamin D-deficient people have increased odds of having clinically significant depression. Various studies conducted in different parts of the world suggest that irrespective of nutrition intake, longitudinal and latitudinal variation for sun exposure, skin pigmentation, and gender, there is a clear causal relationship between vitamin D status and depression among the healthy general population and establishing that Vitamin D is crucial to mental health [15][16][17][18][19][20]. Regardless of this sufficient evidence, biological mechanisms coupling Vitamin D levels and mental health status are still not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Vitamin D-deficient people have increased odds of having clinically significant depression. Various studies conducted in different parts of the world suggest that irrespective of nutrition intake, longitudinal and latitudinal variation for sun exposure, skin pigmentation, and gender, there is a clear causal relationship between vitamin D status and depression among the healthy general population and establishing that Vitamin D is crucial to mental health [15][16][17][18][19][20]. Regardless of this sufficient evidence, biological mechanisms coupling Vitamin D levels and mental health status are still not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, data were obtained from the Chinese Early Adolescents Cohort (CEAC) (Wang et al. , 2022 ). The CEAC is an annual three-wave longitudinal study to examine the risk factors associated with emotional and behavioural problems in Chinese early adolescents.…”
Section: Methodsmentioning
confidence: 99%
“…, 2023 ; Wang et al. , 2022 ). However, most previous studies on vitamin D and suicidality matched sex or adjusted sex as a covariate in the statistical models, which would overlook the sex differences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation